2022
DOI: 10.3390/ijerph20010546
|View full text |Cite
|
Sign up to set email alerts
|

Binge Eating Disorder—The Point Prevalence among Polish Women with Polycystic Ovary Syndrome and Validity of Screening Tool for This Population

Abstract: Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders which is associated with an increased risk of metabolic dysregulation. The elevated prevalence of obesity has been observed in women with PCOS. Since obesity is commonly associated with eating disturbances, including the binge eating disorder (BED), and since the hormonal changes in PCOS patients could influence the food intake model, we decided to estimate the prevalence of BED in PCOS patients and to assess the sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Study and participant characteristics are summarized in Table 5 . Six of the included studies were conducted in the United States [ 22 , 70 , 81 , 83 , 93 , 95 ], 6 in the United Kingdom [ 64 , 73 , 78 , 87 , 89 , 94 ], 5 in Turkey [ 66 , 68 , 69 , 74 , 84 ], 4 in Australia [ 28 , 71 , 79 , 92 ], 3 in Sweden [ 65 , 75 , 77 ], 2 in the Netherlands [ 82 , 96 ], and 2 in Poland [ 88 , 91 ]. One each of the remaining studies was conducted in Saudi Arabia [ 85 ], France [ 67 ], Iran [ 72 ], Slovenia [ 97 ], Latvia [ 76 ], Greece [ 86 ], Brazil [ 90 ], and Italy [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Study and participant characteristics are summarized in Table 5 . Six of the included studies were conducted in the United States [ 22 , 70 , 81 , 83 , 93 , 95 ], 6 in the United Kingdom [ 64 , 73 , 78 , 87 , 89 , 94 ], 5 in Turkey [ 66 , 68 , 69 , 74 , 84 ], 4 in Australia [ 28 , 71 , 79 , 92 ], 3 in Sweden [ 65 , 75 , 77 ], 2 in the Netherlands [ 82 , 96 ], and 2 in Poland [ 88 , 91 ]. One each of the remaining studies was conducted in Saudi Arabia [ 85 ], France [ 67 ], Iran [ 72 ], Slovenia [ 97 ], Latvia [ 76 ], Greece [ 86 ], Brazil [ 90 ], and Italy [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different criteria were used to diagnose PCOS in studies. A PCOS diagnosis is defined in the international evidence-based guideline for the assessment and management of PCOS ( Supplemental Table 1 ) and the Rotterdam criteria was the most commonly used criteria in 17 studies [ 22 , 29 , 62 , 69 , 70 , [74] , [75] , [76] , [77] , 82 , [84] , [85] , [86] , 88 , 91 , 93 , [95] , [96] , [97] ]. Eight studies relied upon a self-reported diagnosis or diagnosis found in the participant’s medical chart [ 28 , 64 , 66 , 68 , 73 , 79 , 81 , 92 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations